Pentingnya Edukasi Gizi pada Ibu Hamil yang Mengalami Kekurangan Energi Kronik (KEK) di Desa Tambaan Kec. Camplong Kab. Sampang - Murfi Hidamansyah; Raudhatul Jannah; Ummi Kulsum; Zainun Wahida Fithriani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Pregnant women with Chronic Energy Deficiency (KEK) are in a condition that can affect the health of both the mother and the fetus. KEK in pregnant women increases the risk of Low Birth Weight (LBW) babies, premature birth, maternal and infant mortality. Various efforts have been made to address KEK during pregnancy, yet its prevalence remains high. The aim of this community service is to improve the knowledge and nutritional fulfillment of pregnant women with KEK, as well as the prevention and management of KEK, through education for pregnant women with KEK and also explaining how to improve the nutrition of pregnant women. The target of this community service activity is pregnant women with KEK at the UPTD Camplong Health Center. The implementation of community service was carried out using a quasi-experimental approach with a pre-test and post-test design in the form of questionnaires for all pregnant women. The goal of this activity is to increase pregnant women's knowledge about KEK and balanced nutrition fulfillment. The results and benefits obtained from this community service activity include educating about fulfilling a balanced diet and improving nutrition, as well as increasing knowledge and insight for the community, especially pregnant women with KEK. The conclusion of this community service activity is that education and assistance can be an effective strategy to improve the health of pregnant women with KEK.